2017
DOI: 10.1101/164335
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Safety and Lack of Negative Effects of Wearable Augmented-Reality Social Communication Aid for Children and Adults with Autism

Abstract: There is growing interest in the use of augmented reality (AR) to assist children and adults with autism spectrum disorders (ASD); however, little investigation has been conducted into the safety of devices for AR such as smartglasses. The objective of this report was to assess the safety and negative effects of the Brain Power Autism System (BPAS), a novel AR smartglasses-based social communication aid for people with ASD. A sequential series of 18 children and adults aged 4.4 to 21.5 years (mean 12.2 years) … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
2
2

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 39 publications
(52 reference statements)
0
17
0
1
Order By: Relevance
“…15 AR rehabilitation approaches have been growing in recent years promoting increase in selective and sustained attention 16 and active participation in realistic and interactive simulations. 17 This has led to research interests in a range of everyday adaptive living situations, including living tasks, such as brushing their teeth independently, 18 interventions to enhance social communication, 19 and promotion of greeting skills. 20 One significant recent study is that of Guarnieri et al 21 in which an AR game called ''MoviLetrando'' was presented and demonstrated feasibility and reliability in use with 88 intellectually disabled young individuals, together with the game's ability to provide similar and precise results on test-retest trials.…”
Section: Introductionmentioning
confidence: 99%
“…15 AR rehabilitation approaches have been growing in recent years promoting increase in selective and sustained attention 16 and active participation in realistic and interactive simulations. 17 This has led to research interests in a range of everyday adaptive living situations, including living tasks, such as brushing their teeth independently, 18 interventions to enhance social communication, 19 and promotion of greeting skills. 20 One significant recent study is that of Guarnieri et al 21 in which an AR game called ''MoviLetrando'' was presented and demonstrated feasibility and reliability in use with 88 intellectually disabled young individuals, together with the game's ability to provide similar and precise results on test-retest trials.…”
Section: Introductionmentioning
confidence: 99%
“…Given the proximity of smartglasses to the sensory organs contained in the human head, this type of computing may enable a higher level of human-computer interaction than other devices [13]. Smartglasses are already being developed as a social and behavioral communication aid for people with ASD [8,15,16]. …”
Section: Introductionmentioning
confidence: 99%
“…Glass has been creatively developed as a technology that can deliver social and cognitive skills coaching to children and adults with ASD [8]. To our knowledge, we have reported on the first studies of ASD-related software on the original Google Glass (Explorer Edition) [8,9,15,16], and here we present the first appearance of Glass (Enterprise Edition) in the literature.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations